Heteronomías en las ciencias sociales : procesos investigativos y violencias simbólicas - Valenzuela Arce, José Manuel, 1954- (Temas CLACSO, 2020)
This work does not seek to question or discredit the essential academic activity, nor its enormous social contributions, nor to fail to recognize the serious, rigorous and socially relevant work that a large number of social scientists have carried out and are carrying out. We know and recognize that a lot of effort, knowledge and commitment are put into the social sciences in order to solve economic, political, psychosocial and ecological problems and that this work is carried out on a daily and systematic basis by colleagues who work with enormous social empathy and respect for the communities, groups or social sectors with whom they investigate. However, we also recognize important biases inscribed in the scientific field itself where orientations linked to neoliberal approaches to science prevail, where beyond the theoretical perspective with which it is investigated, the monological neoliberal imprint predominates.